Not by science, but by Spirit? African Pentecostal prophets and prosperity in the Fourth Industrial Revolution era - Banda, Collium (Stellenbosch Theological Journal, 2023)
Many Africans rely on the spiritualistic solutions offered by the African neo-Pentecostal prophets (ANPPs) to navigate their socioeconomic realities. This article critically evaluates the efficacy of the ANPPs’ spiritual approach within the economic landscape of the Fourth Industrial Revolution (4IR). The essay delves into the extent to which these prophets’ spiritual perspectives on economic matters equip Africans to meaningfully engage in the evolving 4IR economy, driven by artificial intelligence (AI) and scientific technologies. It seeks a theological framework for economic life that can guide ANPPs in offering avenues for economic engagement that empower Africans to participate effectively in the 4IR-based economy. It is argued that the ANPPs’ spiritualistic approach to economic life disempowers Africans from effectively participating in the 4IR economy. ANPPs are thus urged to incorporate science and technology into their economic worldview.